Architectural Drawings: Sources for Urban History - Ahlgren, Dorothy (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1983)
Architectural drawings are among those documents not yet utilized extensively by urban historians. In addition to possessing aesthetic properties, graphic architectural records are valuable sources of information communicated both overtly and covertly. They provide data directly related to the structure, such as its location, dimensions, owner and architect. More subtly, architectural drawings convey an impression about the scale of structures, their style and the philosophy of the architect involved. This article, using examples from collections at the Public Archives of Canada, suggests how architectural drawings might contribute to urban history.